Dry grasslands of Hippocrepido glaucae-Stipion austroitalicae in the Pollino Massif (Calabria, Italy) - Terzi, Massimo; D’Amico, Franceso S. (Acta Botanica Croatica, 2016)
Rocky pastures dominated by Stipa austroitalica in the south-east of Italy were classified within an endemic alliance, Hippocrepido glaucae-Stipion austroitalicae, originally assigned to a Balkan order (Scorzoneretalia villosae). Actually, the distribution area of S. austroitalica extends further westwards and large patches are found on the south-east side of the Pollino Massif. This study aims to describe and characterise the plant communities dominated by S. austroitalica in this area and analyse their floristic and chorological relationships with other associations of Hippocrepido-Stipion. Moreover, their syntaxonomy is discussed in the context of the Italian and south European dry grasslands biogeography. The grasslands were studied on the basis of 19 phytosociological relevés. A larger data set, including 185 relevés with S. austroitalica, was used to visualise the relationships among the associations through nonmetric multi-dimensional scaling ordination. The results allowed the description of a new association, Bupleuro gussonei-Stipetum austroitalicae, classified within Hippocrepido-Stipion. As a consequence, the alliance synrange was extended up to the Pollino Massif. The Hippocrepido-Stipion, together with Cytiso spinescentis-Bromion erecti, was arranged in Euphorbietalia myrsinitidis, an endemic order of the Italian peninsula. The proposed scheme upgrades the syntaxonomy and nomenclature of the dry grasslands vegetation of central and southern Italy.